Ethical purchase behaviour and social responsibility in business - Smith, N. Craig (Cranfield University, 1985)
This thesis is about the decisions made in markets: whether decisions and what decisions are made by consumers. It isa study in consumer sovereignty and particularly In the way this may be used In ensuring social responsibility In business. Pressure group influence on purchase behaviour, particularly in the use or threat of consumer boycotts, suggests an extension of consumer sovereignty beyond its mere technical meaning within economics to a more literal meaning. Consumer authority in the marketplace may not simply refer to the more immediate characteristics of the offering such as product features or price but, as boycotts show, other charac- teristics such as whether the firm has investments in South Africa. Consumer boycotts are but the most manifest and organised form of purchase behaviour influenced by ethical concerns. Yet ethical purchase behaviour, although found in many markets, is largely unre- cognised In the literature. The novelty of this topic and the perspective on consumer sovereignty entailed an emphasis on conceptualisation in the research. The nature of capitalism and consumer sovereignty, the ideology of marketing, the problem of the social control of business, and pressure groups in the political process and their strategies and tactics, are explored to develop an argument which supports the notion of ethical purchase behaviour. A model is proposed identifying a role for pressure groups In the marketing system, explaining ethical purchase behaviour at the micro level by recognising negative product augmentation. Survey research and case studies support the model and the argument. Guidelines for action are proposed for pressure groups and business, suggesting both seek to influence a legitimacy element in the marketing mix. At a more conceptual level, consumer sovereignty is shown to offer potential for ensuring social responsibility in busi - ness. Of the three mechanisms for social control of business, the market may be used to greater effect through ethical purchase beha- vi our. However, consumer sovereignty requires choice as well as information. Pressure groups may act as a countervailing power by providing the necessary information, but competition is essential for choice. Consumer sovereignty Is the rationale for capitalism, the political- economic system in the West. This study questions the basis of such a system if political or ethical, as well as economic decisions, are not made by consumers in markets. Hence the argument for ethical purchase behaviour becomes an argument for capitalism.